Corporate Strategy for Quality GHG Emissions Disclosure: A Systematic Review - Wahyuni, Sri; Irianto, Gugus; Darmawan, Arief; Andayani, Wuryan; Baridwan, Zaki (International Journal of Energy Economics and Policy, 2025)
This systematic review analyses the factors that influence the quality of corporate GHG emissions disclosure and strategies for improvement. The research methodology includes English-language scientific articles (2014-2025) from the Scopus and Web of Science databases that explicitly discuss GHG emissions disclosure. From 128 studies that passed the Cohen’s Kappa reliability test, thematic analysis using NVivo 15 identified four main categories: Drivers, barriers, enablers, and outcomes of disclosure. The findings show that external factors such as regulations and stakeholder pressure are the main drivers of disclosure. However, the absence of uniform regulations and limitations in companies’ internal capacity to manage emissions data remain major challenges. The analysis recognized adopting innovative technologies, external audits, and enhancing corporate governance. Integrating these universally improves corporate reputation, finances, and value, and decreases the cost of capital. Determining the needs of companies in developing transparent and credible reports on emissions. This study proposes a GHG disclosure strategy matrix as a practical guide for companies in formulating more transparent and credible emissions reports. The resulting matrix is expected to serve as a strategic instrument for improving the accuracy and transparency of corporate emissions reporting.